2004
DOI: 10.1021/jp048305d
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and Conformations of α-Helical Human Apolipoprotein CI on Hydrophilic and on Hydrophobic Substrates

Abstract: Interactions between amphiphilic R-helical human apolipoprotein CI (APO CI) adsorbed on hydrophilic and on hydrophobic surfaces were studied using an interferometric surface force apparatus in an effort to understand the surface conformation and the binding activity of this protein. We used mica as the hydrophilic substrate and polymerized octadecyltriethoxysilane (OTE)-covered mica as the hydrophobic substrate. The OTE monolayer and the OTE Langmuir-Blodgett film were studied using Brewster angle microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…These protein segments could take part in bridging between the two surfaces and thus be responsible for the attractive force. This kind of attractive force was also observed in adsorbed surfaces with Apo CI (Campos-Terán et al, 2004). In addition, studies of Apo AII and Apo CI monolayers have shown that it is possible to form a layer with protruding segments at an interface (Bolaños-García et al, 2001;Ruíz-García et al, 2003).…”
Section: Short-range Forces Probe the Orientation Of The Adsorbed Promentioning
confidence: 60%
See 3 more Smart Citations
“…These protein segments could take part in bridging between the two surfaces and thus be responsible for the attractive force. This kind of attractive force was also observed in adsorbed surfaces with Apo CI (Campos-Terán et al, 2004). In addition, studies of Apo AII and Apo CI monolayers have shown that it is possible to form a layer with protruding segments at an interface (Bolaños-García et al, 2001;Ruíz-García et al, 2003).…”
Section: Short-range Forces Probe the Orientation Of The Adsorbed Promentioning
confidence: 60%
“…This experiment showed the reversibility of Apo AII adsorption process that produces in each stage different protein conformations. Also, it is noteworthy that quite similar force curves were observed in Apo CI (Campos-Terán et al, 2004), which also has a similar secondary structure but with a different peptide sequence, different net charge, and it is only monomeric. Therefore, the observed force curves seem to be a consequence of the particular features of the amphiphilic -helices.…”
Section: Sequential Addition Of Apos Builds Up Protein Multilayersmentioning
confidence: 60%
See 2 more Smart Citations
“…With regards to BP, Cinvestav's physics department is already developing a research core [34][35][36][37][38][39], which other departments at Cinvestav are also doing research in biological physics and related issues [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. We also should account for the work at the biophysics group in the Instituto de Física y Matemáticas of the Universidad Michoacana San Nicolás Hidalgo [58], as well as the Instituto de Ciencias Físicas [59][60][61][62][63][64][65][66][67][68][69][70][71][72], Instituto de Física [73][74][75][76], and Facultad de Ciencias [77,78], all three at UNAM. Some very recent endeavors in biological physics research are under gestation at the División de Ciencias e Ingeniería at Universidad de Guanajuato in León (DCI-UG, formerly UG Physics Institute, IFUG...…”
Section: Some Historical Remarks On Biological Physics Méxicomentioning
confidence: 99%